DEIXIS ANALYSIS OF MONOLOGUE ACTION IN EPISODE 26 OF “NEON GENESIS: EVANGELION” ANIME ENGLISH DUB VERSION - Setyawan, Moch. Rafie Dhia; Surista, Ade (Jurnal Bahasa Asing, 2025)
The research is about deixis used in the Japanese cartoon or we all known as “anime” namely “Neon Genesis: Evangelion” by Hideaki Anno that appears in some particular scene during the monologue action of main character named Shinji Ikari. This research aims to identify the types and meanings of deixis employed in the anime, specifically in the final episode, titled “Episode 26: Take Care of Yourself.” This research employs Levinson's theory, which classifies deixis into four types: personal deixis, temporal deixis, spatial deixis, and social deixis. The researcher employed a qualitative descriptive methodology. The data was collected through an observational gathering method accompanied by a note-taking technique. The analysis revealed the presence of personal deixis, temporal deixis, and spatial deixis in the five-minute monologue of Shinji Ikari in episode 26 of the English dub of “Neon Genesis: Evangelion” by Hideaki Anno. Personal deixis predominates in the total number of deictic words.